Implementing service-improvement change in Irish hospitals : exploring facilitating and hindering factors - McDermott, Aoife (Trinity College (Dublin, Ireland). Trinity Business School, 2008)
The principal objectives of this thesis are (1) to identify who holds change-related roles, how are they enacted in and affected by role-related constraints and what works effectively; (2) To identify the contextual factors beyond role level that facilitate or hinder the implementation of service-improvement change; and (3) To explore whether there are there systematic differences between voluntary, public and private hospitals in the dimensions considered above. Fundamentally the research is concerned with the initiation and implementation of service-improvement initiatives through people, w/ho act within constraints.
Keywords: Business Studies, Ph.D.; Ph.D. Trinity College Dublin